2020
DOI: 10.33865/ijcrt.002.01.0373
|View full text |Cite
|
Sign up to set email alerts
|

A Line × Tester analysis for some seed cotton yield and fiber quality traits in upland cotton

Abstract: The objective of the present study was to estimate general combining ability (GCA) of the parents and specific combining ability (SCA) of crosses for the development of high yielding cotton varieties. The study was carried out at the experimental area of Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad. A line × tester analysis was made to identify the superior general and specific combiners for seed cotton yield and fiber quality traits in upland cotton. Five lines/females (FH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Boyaci (2011) reported that fiber fineness, boll seed weight and earliness characteristics showed negative heterosis, while both positive and negative heterosis could be seen in other characteristics. In addition, many researchers determined that non-additive genes, in other words, dominant, epistatic or dominant × epistatic genes were effective in the management of yield, ginning percentage, earliness, single boll seed weight, 100 seed weight, fiber fineness and fiber strength traits in Line × Tester populations (Ashokkumar et al, 2010;Saravanan et al, 2010;Kalpande et al, 2014;Sawarkar et al, 2015;Sajjad et al, 2016;Guvercin, 2016;Patil et al, 2018;Ullah et al, 2020;Unay et al, 2020). Basal et al (2009) and Karademir et al (2009) reported that fiber length is managed by additive genes.…”
Section: Introductionmentioning
confidence: 99%
“…Boyaci (2011) reported that fiber fineness, boll seed weight and earliness characteristics showed negative heterosis, while both positive and negative heterosis could be seen in other characteristics. In addition, many researchers determined that non-additive genes, in other words, dominant, epistatic or dominant × epistatic genes were effective in the management of yield, ginning percentage, earliness, single boll seed weight, 100 seed weight, fiber fineness and fiber strength traits in Line × Tester populations (Ashokkumar et al, 2010;Saravanan et al, 2010;Kalpande et al, 2014;Sawarkar et al, 2015;Sajjad et al, 2016;Guvercin, 2016;Patil et al, 2018;Ullah et al, 2020;Unay et al, 2020). Basal et al (2009) and Karademir et al (2009) reported that fiber length is managed by additive genes.…”
Section: Introductionmentioning
confidence: 99%